2018
DOI: 10.1530/jme-17-0304
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of beneficial effects of metformin on fatty acid-treated human islets

Abstract: Elevated levels of palmitate accentuate glucose-stimulated insulin secretion (GSIS) after short-term and cause beta-cell dysfunction after prolonged exposure. We investigated whether metformin, the first-line oral drug for treatment of T2DM, has beneficial effects on FFA-treated human islets and the potential mechanisms behind the effects. Insulin secretion, oxygen consumption rate (OCR), AMPK activation, ER stress and apoptosis were examined in isolated human islets after exposure to elevated levels of palmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…In addition, oxidative enhancement of FFA inhibits glucose from entering tissue cells by altering the REDOX potential of cells and inhibiting some key enzymes responsible for glycolysis and citric acid cycle. Thus, long-term increase of FFAs can exert cytotoxic and pro-apoptotic effects on human islet cells, inhibit the activity of phosphoinositi-3 kinase, affect the insulin receptor after signal transmission system, leading to dysfunction of glucose transporter and IR ( 31 ). Therefore, high levels of FFA and IR interact together to promote the occurrence and development of MS. Studies have found that the level of FFA 16:0 (palmitoleic acid) in plasma and follicular fluid of obese PCOS patients was higher than that of the control group and non-obese PCOS patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, oxidative enhancement of FFA inhibits glucose from entering tissue cells by altering the REDOX potential of cells and inhibiting some key enzymes responsible for glycolysis and citric acid cycle. Thus, long-term increase of FFAs can exert cytotoxic and pro-apoptotic effects on human islet cells, inhibit the activity of phosphoinositi-3 kinase, affect the insulin receptor after signal transmission system, leading to dysfunction of glucose transporter and IR ( 31 ). Therefore, high levels of FFA and IR interact together to promote the occurrence and development of MS. Studies have found that the level of FFA 16:0 (palmitoleic acid) in plasma and follicular fluid of obese PCOS patients was higher than that of the control group and non-obese PCOS patients.…”
Section: Resultsmentioning
confidence: 99%
“…fasting blood glucose (FBG) ≥5.6 mmol/L, or having been diagnosed with diabetes. The HC group had regular menstrual cycles(27)(28)(29)(30)(31)(32)(33)(34)(35) days) without Abbreviation: PCOS, polycystic ovary syndrome; MS, metabolic syndrome; UPLC, ultraperformance liquid chromatography; ROC, the receiver operating characteristic; T2DM, type 2 diabetes; CVD, cardiovascular disease; BMI, body mass index; FINS, fasting insulin; HDL, high density lipoprotein; HC, healthy control; WC, waist circumference; TG, triglyceride; SBP, systolic blood pressure; DBP, diastolic blood pressure; FBG, fasting blood glucose; FSH, follicle stimulating hormone; LH, luteinizing hormone; TT, total testosterone; DHEAS, dehydroepiandrosterone sulfate; A2, androstenedione; SHBG, sex hormone binding globulin; HOMA-IR, homeostatic model index of insulin resistance; Zhao et al Screen Metabolic Syndrome of PCOS clinical or biochemical manifestations of hyperandrogen. Besides, women who had adrenal, thyroid, and pituitary dysfunction or who used medications that interfered with endocrine, blood pressure, lipid, or carbohydrate metabolism during the first six months, such as oral contraceptives, androgen preparations, insulin sensitizers, iron supplements were excluded from the study.…”
mentioning
confidence: 99%
“…We first reported that serum MANF levels were dramatically increased in women with PCOS after metformin therapy, and the increase was accompanied by the improvement of insulin sensitivity and hyperandrogenism. Since much evidence has demonstrated that metformin ameliorates ERS [4,26], we predict that metformin may reduce the degradation of MANF by alleviating ERS. A recent study in mice found that MANF supplementation reduced the markers of inflammation and cellular damage, and improved glucose tolerance and insulin tolerance [10].…”
Section: Discussionmentioning
confidence: 95%
“…It has been established that prolonged exposure to palmitate impairs GSIS and contributes to β-cell dysfunction. Human islet cells in culture for seven days with palmitate showed a reduction of p-AMPK and a significant elevation of phosphorylated eukaryotic initiation factor-2 (p-EIF2α), CHOP, and cleaved caspase 3, but their levels were normalized in the presence of 25 µM metformin [ 75 ]. This suggests metformin is able to improve chronic fatty acid exposure-induced pancreatic β-cell dysfunction.…”
Section: Metformin Improves Pancreatic β-Cell Functionmentioning
confidence: 99%